Concomitant bacteremia in adults with severe falciparum malaria - Phu, NH; Day, NPJ; Tuan, PQ; Mai, NTH; Chau, TTH; Van Chuong, L; Vinh, H; Loc, PP; Sinh, DX; Hoa, NTT; Waller, DJ; Wain, J; et al. (Oxford University Press, 2020)
Background Approximately 6% of children hospitalized with severe falciparum malaria in Africa are also bacteremic. It is therefore recommended that all children with severe malaria should receive broad-spectrum antibiotics in addition to parenteral artesunate. Empirical antibiotics are not recommended currently for adults with severe malaria.